Effect of transcutaneous electrical nerve stimulation (TENS) on knee pain and physical function in patients with symptomatic knee osteoarthritis: the ETRELKA randomized clinical trial. Issue 3 (March 2022) - Reichenbach, S.; Jüni, Peter; Hincapié, C.A.; Schneider, C.; Meli, D.N.; Schürch, R.; Streit, S.; Lucas, C.; Mebes, C.; Rutjes, A.W.S.; da Costa, B.R.
Summary: Objective: To determine the effectiveness of TENS at relieving pain and improving physical function as compared to placebo TENS, and to determine its safety, in patients with knee osteoarthritis. Methods: Multi-centre, parallel, 1:1 randomized, double-blind, placebo-controlled clinical trial conducted in six outpatient clinics in Switzerland. We included 220 participants with knee osteoarthritis recruited between October 15, 2012, and October 15, 2014. Patients were randomized to 3 weeks of treatment with TENS ( n = 108) or placebo TENS ( n = 112). Our pre-specified primary endpoint was knee pain at the end of 3-weeks treatment assessed with the WOMAC pain subscale. Secondary outcome measures included WOMAC physical function subscale and safety outcomes. Results: There was no difference between TENS and placebo TENS in WOMAC pain at the end of treatment (mean difference −0.06; 95%CI -0.41 to 0.29; P = 0.74), nor throughout the trial duration ( P = 0.98). Subgroup analyses did not indicate an interaction between patient/treatment characteristics and treatment effect on WOMAC pain at the end of treatment ( P -interaction ≥0.22). The occurrence of adverse events was similar across groups, with 10.4% and 10.6% of patients reporting events in the TENS and placebo TENS groups, respectively ( P = 0.95). No relevant differences were observed in secondary outcomes. Conclusions: TENS does not improve knee osteoarthritis pain when compared to placebo TENS. Therapists should consider other potentially more effective treatment modalities to decrease knee osteoarthritis pain and facilitate strengthening and aerobic exercise. Our findings are conclusive and further trials comparing TENS and placebo TENS in this patient population are not necessary.